How Human Capital Development And Environmental Degradation Influence Economic Growth? (Journal of Namibian Studies : History Politics Culture, 2023)
This study investigates the relationship between human development, environmental quality, and economic growth in 32 UFM countries over the period 1990-2019. The countries are divided into developed and developing categories. A panel model is employed, considering CO2 emissions, Modified Human Development Index (MHDI), financial development, trade openness, domestic capital, and labor force as determinants of economic growth. The findings reveal that environmental degradation has a negative impact on economic growth in both developed and developing countries. Financial development is found to have a positive effect on economic growth, indicating the importance of a well-developed financial system. Trade openness is positively associated with economic growth, particularly in developed countries. Domestic capital and the labor force have positive effects on economic growth in both country groups. The study suggests the implementation of effective environmental policies, investments in human development, promotion of financial sector development, trade liberalization, and infrastructure investment as key policy implications for sustainable and inclusive economic growth.